perancangan convention dan exhibition di solo dengan pendekatan metafora - irfan siswanto; Anggraeni Dyah Sulistiowati (MAESTRO, 2019)
Because the city of Solo has great business potential, stable economic growth, the number of tourism that continues to increase and successful city branding, the development in the city of Solo continues to grow. One of the developments planned by the government is MICE development in the city of Solo. MICE stands for "Meeting, Incentive, Convention, and Exhibition". In Indonesian means meetings, incentives, conventions and exhibitions. In the tourism industry or exhibition, MICE is a type of tourism activity in which a large group, usually planned carefully, departs together for a particular purpose. Thus the convention and exhibition buildings will be designed in the city of Solo. With the existence of Convention and Exhibition buildings in Solo, the people of Solo and surrounding areas have a place to conduct convention and exhibition activities.